Characterization and resistance pattern of bacterial isolates from pus samples in a tertiary care hospital, Karimnagar - Sirigadha, Krishnamurthy; Sajjan, Amar C; Ms Swetha; S, Shalini (Tropical Journal of Pathology and Microbiology)
Background: Wound infection can cause delayed healing, chronicity which indirectly causes financial burden and psychological stress on patients. Aim: To speciate the organism isolated from pus sample received and its antibiotic sensitivity test. Methods and materials: All isolated organism are identified by colony morphology, Gram stain and biochemical reactions. Antibiotic sensitivity test for all isolates were done by Kirby-Bauer method using Mueller Hinton agar. Results: The major contribution of sample was from surgery department (65.3%) followed by orthopedics (10.2%). A total of 383 organism isolated among which Klebsiella pneumoniae dominates (34.46%) followed by Staphylococcus aureus (18.53%). All Gram negative organisms showed maximum resistance to amoxyclav and least to Imipenem. All Gram positive organisms showed least resistance to Vancomycin and Linezolid. Pseudomonas aeruginosa showed maximum resistance to amoxyclav (66.1%) and Gentamicin (57.1%) and least to Imipenem (7.1%). Conclusion: It is observed from the present study that, there is an increase in the resistance among beta-lactam antibiotics and quinolones. Emergence of drug resistance can be effectively controlled by continuous surveillance in hospitals and rational use of antibiotics.